Project Manager Profile Characterization in the Construction Sector in Bogotá, Colombia - Giraldo González, Germán Eduardo; Pulido Casas, Gabriel Humberto; Leal Coronado, César Augusto (Project Management Institute, 2013)
This study aims to describe and evaluate the characteristics (educational background, training, skills, and experience) that make up the project manager profile in the construction sector in Bogotá, Colombia. This study is based on a project management literature review, expert interviews and surveys with a group of project managers in the construction sector, and comparisons between them. This evaluation aims to contribute to the development of a clearer definition of the project manager profile in the Colombian context. The identified project manager profile satisfies the essential desired characteristics with some particular weaknesses related to education and training in project management.

Este estudio tiene como objetivo describir y evaluar las características (formación académica, capacitación, competencias y experiencia) que conforman el perfil del gerente de proyectos en el sector de la construcción en Bogotá, Colombia. Este estudio se basa en una revisión bibliográfica sobre gestión de proyectos, entrevistas a expertos y encuestas a un grupo de gestores de proyectos del sector de la construcción, así como en comparaciones entre ellos. Esta evaluación pretende contribuir al desarrollo de una definición más clara del perfil del gestor de proyectos en el contexto colombiano. El perfil de gerente de proyecto identificado satisface las características esenciales deseadas con algunas debilidades particulares relacionadas con la educación y formación en gerencia de proyectos.
Keywords: Project manager; Profile; Competencies; Construction; Colombia